Features of the use of instrumental methods of problem analysis when implementing lean manufacturing - A. V. Gerasimov; Zh. A. Mingaleva (Управление)
Successful implementation of the lean manufacturing concept at an enterprise is impossible without the use of special management tools that allow timely identification of problems in the organisation’s activities and causes of their occurrence. However, the increase in uncertainty and unreliability of information creates significant obstacles in making both quick and accurate decisions. The need to select analytical tools to improve the reliability of management decisions requires careful choice of methods for making them. The article analyses the strengths and weaknesses of the Ishikawa cause-effect diagram as an instrumental method of this process for improving production processes. With the help of the comparative analysis based on the use of the Ishikawa diagram, four problems have been identified that may underlie the inhibition of managerial decision-making. The advantages and disadvantages of applying this method in the field of enterprise management and decision-making in conditions of high-speed changes in the external environment are analysed. The most popular modifications of the Ishikawa diagram are considered. It is concluded that the Ishikawa diagram is an effective tool for making prompt and strategic decisions to improve production processes as well as to increase the success of implementing lean manufacturing principles.